An insight into an intriguing oxidative biotransformation pathway of 5-O-caffeoylquinic acid by a gut bacterium. Issue 11 (18th May 2022) - Balaj, G.; Tamanai-Shacoori, Z.; Olivier-Jimenez, D.; Sauvager, A.; Faustin, M.; Bousarghin, L.; David-Le Gall, S.; Guyot, S.; Nebija, D.; Tomasi, S.; Abasq, M. L.
Abstract : A molecular networking analysis of 5-CQA biotransformation by L. reuteri highlighted its bioconversion into esculetin by an oxidative pathway. Esculetin has been also identified after electrochemical or enzymatic oxidation of caffeic acid. Abstract : Microbiota is known to play a pivotal role in generating bioavailable and bioactive low-molecular-weight metabolites from dietary polyphenols. 5- O -caffeoylquinic acid (5-CQA), one of the main polyphenols found in human diet, was submitted to a resting cell biotransformation study using three gut bacteria species Lactobacillus reuteri, Bacteroides fragilis and Bifidobacterium longum . These bacteria were selected according to their belonging to the main phyla found in human gut microbiota. Our study highlighted the ability of only one of the strains studied, L . reuteri, to bioconverse 5-CQA into various metabolites due to the expression of the cinnamoyl esterase enzyme as the first step. Interestingly, one known natural compound, esculetin, was described for the first time as a 5-CQA-derived metabolite after conversion by a gut bacterium, the other metabolites had already been reported. This evidence highlighted an interesting oxidative pathway occurring in vivo by intestinal microbiota leading to esculetin. This molecule was also identified after electrochemical and enzymatic oxidations of caffeic acid. The oxidation capacity of L . reuteri led to less diverse metabolites in comparison to those obtained either electrochemically and enzymatically where dimers and trimers were reported. Thus, esculetin may have interesting and benefical biological effects on gut microbiota, which should be further evaluated. Novel synbiotics could be formulated from the association of L . reuteri with 5-CQA.